The Relationship Between Mastery of Arabic Vocabulary and Speaking Skill for Eleventh Grade Students at Trubus Iman High School for Girls Paser - Hasanah, Azyyati Uswatun; Yamin, Muhammad (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2021)
In learning Arabic, it does not only require knowledge in terms of qowaid or Arabic grammar. But we also have to learn and multiply the Arabic vocabulary. By increasing the Arabic vocabulary, it will be easier for someone to improve their Arabic skills, especially in speaking skills. In this paper, the author examines how the mastery of Arabic vocabulary and speaking skills of students of 11th Grade Students at Trubus Iman High School For Girls Paser. And how is the relationship between mastery of Arabic vocabulary and speaking skills of students of Eleventh Grade Students at Trubus Iman High School For Girls Paser. This research is a field research, which uses quantitative analysis with the product moment correlation formula from Pearson to answer the problems in this research. The results of this study indicate that there is a correlation relationship in the